ANALISIS UNSUR-UNSUR TINDAK PIDANA PENCURIAN: TINJAUAN HUKUM - Hamdiyah, Hamdiyah (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
This research aims to find out about the crime of theft and the elements of the crime of theft. The research method used is the library method by collecting various documents. The research results show that the crime of theft is an unlawful act that involves taking goods or property belonging to another person without permission or legal rights. This phenomenon covers varying degrees of severity, from petty theft to robbery. Theft can harm individuals and society at large. To tackle this crime, preventive measures are needed, such as increasing security and public awareness. The legal system regulates the elements of theft and provides appropriate sanctions depending on the severity of the legal violation. The elements of the crime of theft include the act of taking goods owned by another person, intent to possess, against rights or without permission, transfer of ownership, and the context of the criminal article. All of these elements must be met for an act to be considered theft according to the law. By fulfilling these elements, the law can determine whether a person is guilty of committing the crime of theft and provide appropriate sanctions.